Seleção de meio de cultura para determinação da viabilidade de bifidobactérias durante a vida de prateleira de bebida láctea fermentada com soro de leite nanofiltrado - Beatriz Silva Pereira (2012)
Production of fermented lactic beverages added with cheese whey has been favored by consumers quest for healthy foods and by the use of whey in dairy industry. Dairy industry aiming functional foods production being added probiotics cultures, which should present the minimum counting of viable cells of 106 CFU.g-1 of the product at the time of consumption. It is extremely important to evaluate methods for quantification of these probiotic strains. Culture media (Gentamicin-MRS, Dicloxaciline-MRS, Bile-MRS, NNLP-MRS, Maltose-MRS and LP-MRS) were evaluated for ability to selective enumeration of different bifidobacteria strains (B. longum 51A, B. bifidum 1622A, B. breve1101A, and B. pseudolongum 1191A). Viability of Bifidobacterium strain, starter culture, and acidity, pH and syneresis were monitored during storage (5°, 28 days). G-MRS and Bile-MRS medium significantly inhibited (p<0,05) L-812 starter culture and showed good probiotic strains recovery, without statistic difference to the standard medium (MRS). However, Bile-MRS showed the best Bifidobacterium recovery (94%) and the best inhibition of the starter culture (L-812). This was the medium used for enumeration of probiotic microorganisms in the presence of L-812 culture. In the shelf-life study, pH lowered significantly in the first week only, dropping from 4.8 (time 0) to 4.21 (7 days). Only beverage added with B. pseudolongum 1191A had acidity increased on the 14th day, remaining stable until the 28th day. Syneresis has lowered 6.05% for the four lactic beverages. Lactic acid-bacteria count remained above 8.0 Log CFU.mL-1 over time. For Bifidobacterium spp. viability, all the strains decreased from less than 6.0 log CFU.mL-1 from the 7th day of analysis, allowing no probiotic beverage characterization. The lacticbeverages showed good storage stability, although other variables are to be explored in order to find a food matrix in which probiotic strains remain viable.